Kelangkaan (Scarcity) Ekonomi: Perbedaan dan Kecocokan Perspektif Islam - Dafiar Arif; Wawan Devis Wahyu; Ahmad Yani; Yuse Rizal Bustami; Dafid Hidayat (Tasharruf : Journal of Islamic Economics and Business, 2023)
The causes of scarcity in the economy have two different opinions, firstly due to insufficient natural resources to meet human needs, secondly due to reasons of unequal distribution while natural resources are sufficient to meet human needs, these two arguments argue against each other and claim to be the most correct. The purpose of this study is to look at the causes of scarcity in terms of phenomena and in terms of texts (the Koran and hadith) and equate the two opinions. The method used in answering this problem is normative and sociological qualitative methodology, namely research based on the Koran and using analysis of an object problem, as well as understanding (understanding) phenomena or social symptoms. By collecting various literature that has been published using the Publis or Perish application, it is continued to analyze the results of the literature on the factors of scarcity using the Nvivo application tool, then the results are reviewed from the arguments of the Koran and hadith. The results of this study found that scarcity caused by natural resources, population, experts and unequal distribution, these four causes have the truth in the textual postulate.